Solution of an infinite system of differential equations. - Ibragimov , G. I.; Allahabi , Fateh Abdo Ali (Pushpa Publishing House, 2009)
We consider an infinite system of differential equations of the second order. Existence and uniqueness questions are discussed in the Hilbert space. We obtain a result which enables the investigation of optimal control and differential game problems described by such a system.